Você está na página 1de 2

# Reduction Formula

1.

x 2n

In =

(a)

Prove that

(i)

(b)

By considering

Jn + Jn-1

1 x2

dx

J0 =

2.

If

un =

If

In =

/ 2

Evaluate
3.

If

If

1 x2

(ii)

and

xn

a +x

## , show that the reduction formula for

In

allows

Jn

to be evaluated

n.

74 2

16

.
un =

1
n

n 1
n

u n 2 .

u5 .

dx

x5
5 + x2

( n = 0, 1, 2, 3, )

dx

## x cos n xdx , where n > 1 , show that

u4

In =

, show that

x n 1
n

a2 + x2

n 1
n

a 2 I n 2 , where

n2.

dx .

1/ 2

/ 2

Evaluate
5.

Evaluate
4.

J3 =

Prove that

x 2n

I0

(c)

(1 + x )

Jn =

and

1/ 2

## (n + 2) un (2n + 1) aun 1 + x n 1 (2ax x2)3/2 = 0 .

Show that
6.

7.

If

If

In =

x 2 (2ax x 2 ) dx =

2a

1/ 2

xn

3a + x
2

I p ,q =

xp

(1 + x )

2 q

5a 4

dx , show that

(1 + x )

2 3

In =

2a
0

Let

In (z) =

3( n 1)
n

a 2 I n 2 .

x p1

(1 + x 2 )q1

Evaluate

I7 .

+ ( p 1)I p2 ,q 1 .

dx .

9.

2a n

2(q 1)I p ,q =
x6

If

In =

dx , show that

8.

1
0

## Prove that for all

In =

(1 y) n (e yz 1)dy ,
n 1,

I n 1 ( z ) =

z
n

## ( 2 n + 1)( 2 n 1)...7 5 n+2

a
, where
( n + 2)( n + 1)...5 4 2
for all

I n (z) +

is a positive integer.

n0.

z
n ( n + 1)

. Deduce that

ez =

zr

r!
r =0

zn
( n 1)!

I n 1 ( z ) .
1

10.

11.

(a)

(b)

Prove that

If

In =

(a)

(ii)

(iii)

(c)

13.

(a)
(b)

14.

If

x m (ln x ) n dx =

(1 x ) dx
1

2 n

## and use it to evaluate

2 8

( 1)n n!
.
( m + 1)n +1

x n (a 2 x 2 )1 / 2 dx ,

n > 1,

n 1 2
In =
a I n 2 .
n +2

prove that

I4 .

(i)

(b)

(1 x ) dx

Hence find

12.

In =

## Find a reduction formula for the integral

/2

/2

/2

sin 2 n x dx =

2 2 n n! n! 2

sin 2 n+1 x dx =

(2 n )!
2 2 n n! n!

(2 n + 1)!

sin 2 n 1 x dx = 1 +

2n
0<x<

Prove that

Deduce that

/ 2

, then

I ( p, q ) =

/2

/2

/2
0

sin 2 n x dx = 1

## Obtain a reduction formula for

Prove that

sin 2 n x dx = 1 + n

2n

1 n

2n + 1 n 2

/4
0

sin x cos x

sin x + cos x

/2

sin 2 n +1 xdx ,

where

( 2 n )!
2n

2 n!n!

= 1

0 < n < 1 .

1 n

2n + 1 n

2 n +1

dx

## (ln cos x ) cos xdx = ln 2 1 .

( x a ) p (b x ) q dx

(b > a),

## prove that when

n1,

(i)

I(n, n 1) = I(n 1, n)

(ii)

## 2(2n + 1) I(n, n) = 2n (b a) I(n , n 1)

= n(b a)2 I(n 1, n 1).
Hence or otherwise, show that

15.

(5 + x )
2

Prove that

2 3/ 2

(a

dx =

I( n , n ) =

+ x2 )

n/2

( 2 n + 1)!

## dx , where n is an odd positive integer.

396 + 75 ln 5
16

( b a )2 n +1 n!n!